When is indigeneity: closing a legal and sociocultural gap in a contested domestic/international term. (June 2019) - Bello-Bravo, Julia
Indigeneity is a much contested term, complicated by formal definitions under domestic and international law, the unlimited right to self-identification by indigenous people, conflicts and/or contradictions between these legal principles, and the political inequalities that result from variations in access to the processes and legal actions that invoke these terms. In particular, this generates a gap between legal definitions of indigeneity (framed, then and now, by hegemonic powers) and sociocultural practices of indigeneity (expressed and experienced, then as now, by cultures themselves). Reviewing the conceptual framing(s) of indigeneity both internationally and in a domestic (US) context, this article explores and offers a more flexible, resilient, and just understanding of indigeneity capable of closing the legal/sociocultural gap currently affecting indigenous people worldwide. At root, this less means asking what (or where) is indigeneity, and more instead when is indigeneity.